Designing Visually Supported Large-Scale Sensemaking Among Public Servants for Systemic Climate Transitions - Rohit Mondal; Sabrina Bresciani; Nikhil Chaudhary; Ilenia Piergallini; Francesca Rizzo (The International Journal of Design Management and Professional Practice, 2026)
The global challenge of climate change requires governments, regions, and cities to move beyond technical interventions toward socio-technical change through systemic climate transitions. As mission-oriented climate governance encourages municipalities to experiment with and iteratively shape transition pathways, design becomes important as a reflexive practice for building shared understandings of common challenges beyond conventional impact metrics. This study adopts a “Research through Design” approach to design and facilitate visually supported online sensemaking sessions involving over 200 representatives belonging to fifty-three European municipalities across six thematic areas to enable peer-to-peer exchange and learning. Facilitating online sensemaking sessions at this scale requires structured, intentional, and clear visual support. This article reports the outcomes of a visually supported series of sensemaking sessions that enabled large-scale participation of municipalities’ public servants to collectively interpret early-stage implementation challenges, identify shared barriers, and surface transferable practices across diverse local contexts. Cross-cutting insights highlight governance complexity, financing constraints, procurement barriers, data gaps, and the need for trust-building and shared language in stakeholder engagement. The visual scaffolds and metaphors acted as cognitive structures that enabled the exchange of tacit knowledge and fostered shared understandings of common challenges, lessons learned, and the documentation of good practices and opportunities. The study illustrates how structured metaphoric visual support can strengthen large-scale peer learning among municipal planners and policymakers in complex urban climate transitions. This visual facilitation helps city experts share interpretations, learn collaboratively, and iteratively adapt climate action pathways through mission-oriented climate governance and design methods.